Asuhan Kebidanan Pada Ibu Pasca Persalinan Dengan Luka Episiotomi Derajat Ii Ny.P Di Pmb Nurhayati Wilayah Kerja Puskesmas Air Tiris Tahun 2024 - Noraini, Noraini; Syahda, Syukrianti (Evidence Midwifery Journal, 2024)
Episotomy is an incision in the perineum which is carried out immediately before the birth of the baby/during the delivery process. Where this action aims to expand the surface. Efforts to care for episiotomy wounds are very important to prevent infection in the perineal wound. Acceleration in wound healing is highly expected, one of which is by consuming high protrins, namely eggs. This research aims to provide care to postpartum mothers with grade II episiotomy wounds at PMB Nurhayati in the working area of ??the Air Tiris Health Center in 2024. This research is in the form of a case study with a descriptive observational method carried out on Mrs. P at PMB Nurhayati on 09-15 June 2024. The results of the case study research given to Mrs. P, namely seven visits over 1 week. The midwifery care provided is in the form of counseling on how to care for perineal wounds, teaching mothers personal hygiene in the perineum and genitalia area, giving mothers eggs to boil and consume twice every day. Based on the care given to Ny.P, aged 29 years P2A0, it was found that the wound was clean and dry, the suture threads were not visible, there was no tenderness and there were no signs of infection in the perineal wound. In conclusion, the care provided was carried out well and produced positive results. It is hoped that this research can become a reference for readers, researchers and increase insight and develop knowledge regarding care for postpartum mothers with episiotomy wounds.